Ecosynthesis and Optimization of Nano Rgo/Ag-Based Electrode Materials for Superior Supercapacitor Coin Cell Devices - Brito-Ramírez, T (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
In the shift toward sustainable energy, there is a strong demand for efficient and durable energy storage solutions. Supercapacitors, in particular, are a promising technology, but they require high-performance materials that can be produced using simple, eco-friendly methods. This has led researchers to investigate new materials and composites that can deliver high energy and power densities, along with long-term stability. Herein, we report a green synthesis approach to create a composite material consisting of reduced graphene oxide and silver nanoparticles (rGO/Ag). The method uses ascorbic acid, a natural compound found in fruits and vegetables, as a non-toxic agent to simultaneously reduce graphene oxide and silver nitrate. To enhance electrochemical performance, the incorporation of silver nanoparticles into the rGO structures is optimized. In this study, different molar concentrations of silver nitrate (1.0, 0.10, and 0.01 M) are used to control silver nanoparticle loading during the synthesis and reduction process. A correlation between silver concentration, defect density in rGO, and the resulting capacitive behavior was assessed by systematically varying the silver molarity. The synthesized materials exhibited excellent performance as supercapacitor electrodes in a three-electrode configuration, with the rGO/Ag 1.0 M composite showing the best performance, reaching a maximum specific capacitance of 392 Fg−1 at 5 mVs−1. Furthermore, the performance of this optimized electrode material was investigated in a two-electrode configuration as a coin cell device, which demonstrates a maximum areal-specific capacitance of 22.63 mFcm−2 and a gravimetric capacitance of 19.00 Fg−1, which is within the range of commercially viable devices and a significant enhancement, outperforming low-level graphene-based devices. © 2025 by the authors.